KARAKTERISTIK PRODUK HUKUM PERS DAN PROSPEK KONSOLIDASI DEMOKRASI - Triya Indra Rahmawan (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
The press law is legal products that are responsive. It can be seen from the process of formation a press law with participatory manner. The material of press law also has been accomplished with the needs and desires of the people because it gives protection and guarantee against press freedom. In spite of the press law are responsive, but it was still not enforced effectively because it still occurs the practice of violence against practitioners of the press and press freedom abuse. This indicates that the guarantee and protection of press freedom through a press law is still not enough. In this context, the consolidation of democracy requires the existence of an increased public commitment fundamentally to use democratic procedures to organize public spaces that appear in the process of state. Therefore, it takes awareness and commitment together so press freedom can be realized. The Press law needs to be enforced consistently by all elements. The State should provide protection for practitioners by cracking down firmly the perpetrators of violence against practitionersof the press. In addition, the guarantee and protection of press freedom should be balanced with the professionalism of the practitioners of the press, by complying the code ethics of the profession and improve the ability of the press and journalism through education and training because press freedom without the limitations of law and ethics, produce an excessive press freedom.